FREQUENCY OF CARDIAC AUTONOMIC NEUROPATHY IN TYPE 2 DIABETES MELLITUS PATIENTS PRESENTING TO KHYBER TEACHING HOSPITAL PESHAWAR - SAMI, M; SANA, . (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to determine the frequency of cardiac autonomic neuropathy in patients with type 2 diabetes. A cross-sectional study was conducted at the Department of Medicine, Khyber Teaching Hospital Peshawar, Pakistan, from June 2022 to June 2023. The study included 285 individuals aged 40-60 diagnosed with type 2 diabetes for at least 5 to 10 years. The study aimed to evaluate the frequency of cardiac autonomic neuropathy in type 2 diabetics. Chi-square was applied for statistical analysis with a significance level of p≤0.05. Of 285 type 2 diabetic patients, 199 (69.82%) were male, and 86 (30.18%) were female. 26.31% of the participants were diagnosed with cardiac autonomic neuropathy, of which 26.67% were male and 73.33% were female. This difference was statistically significant. 37.35% of the patients with cardiac autonomic neuropathy were smokers, while 62.65% were non-smokers. All the patients with CAN were either overweight or obese. This study found that prolonged diabetes is directly related to the development of cardiac autonomic neuropathy, and there was a statistically significant association between diabetes and gender, as well as smoking.